NEXAFS spectroscopy and spectromicroscopy in the soft X-ray spectral region with a compact laser plasma source based on a double stream gas puff target. (October 2020) - Wachulak, P.; Duda, M.; Bartnik, A.; Węgrzyński, Ł.; Fok, T.; Jancarek, A.; Fiedorowicz, H.
Abstract: The near edge X-ray absorption fine structure (NEXAFS) is an established method employed for a compositional analysis of the samples. The information about sample's elemental composition is obtained through the observation of the soft X-ray (SXR) spectra in the proximity of the high energy side of the X-ray absorption edge of a particular element of interest. This technique allows one to characterize the matter, obtaining useful and important information, such as the structure of intermolecular and atomic bonds in SXR spectral range. The NEXAFS requires, however, short wavelength sources, capable of delivering sufficiently high flux to obtain high quality spectral data. Typical sources for NEXAFS are synchrotrons, free electron lasers, but, more recently, also compact laser produced plasma (LPP) sources; among them, the laser-plasma source based on a double stream gas puff target. In this short review, the application of this source to the recently developed NEXAFS spectroscopy and spectromicroscopy systems will be presented and discussed in more details with the references to the original works. Highlights: NEXAFS spectroscopy around C K-edge with compact LPP SXR source, 2-D spectromicroscopy using an LPP SXR source of EUV etched polymer sample. Single-shot (1 ns), time resolution NEXAFS spectroscopy with an LPP SXR source.